In silico study of columbin from Tinospora crispa L as dihydrofolate reductase-thymidylate synthase (DHFR-TS) inhibitor - Yohanes Bare; Dewi Ratih Tirto Sari; Lydia Efliani Coriessa Meak; Marsiana Coo Mogi (Bioscience, 2022)
The Brotowali plant is used to treat malaria. Tinospora crispa L contains active compounds that are good for health and has been widely used for medicine. Crude extract from Tinospora crispa L can be used as target dihydrofolate reductase-thymidylate synthase (DHFR-TS). This research study was to analyse the potential chemical content of Tinospora crispa L in the form of columbine compounds as a focus of malaria therapy through inhibition of dihydrofolate reductase-thymidylate synthase (DHFR-TS). In silico research method, columbine (CID: 188289) ligand was obtained from Pubchem while DHFR-TS (PDB ID 2bl9) protein was obtained from Protein Data Bank, ligands and proteins were interacted using HEX 8.0.0.0 and visualised using discovery studio. The results obtained are six amino acid residues that bind to the DHFR-TS protein. This binding has an impact on the work function of the DHFR-TS protein. Physicochemical analysis shows that the ligand acts as a donor and acceptor so that the protein is formed and the ligand becomes very strong. This interaction is also supported by amino acid residues that act as supports by forming Van der Waals forces outside of the Van hydrogen bonding forces, pi-Alkyl and Pi also provide support in order to increase the strength and stabilisation of the. Based on the discussion, it can be concluded that the columbine content in Tinospora crispa L has potential as a therapy and treatment for malaria through inhibition of DHFR-TS.Tanaman Brotowali digunakan untuk mengobati penyakit malaria. Tinospora crispa L mengandung senyawa aktif yang baik untuk kesehatan dan telah banyak digunakan untuk pengobatan. Ekstrak kasar dari Tinospora crispa L dapat digunakan sebagai target dihydrofolate reductase-thymidylate synthase (DHFR-TS). Penelitian ini bertujuan untuk menganalisis potensi kandungan kimia Tinospora crispa L berupa senyawa kolumbin sebagai fokus terapi malaria melalui penghambatan dihydrofolate reductase-thymidylate synthase (DHFR-TS). Metode penelitian in silico diperoleh ligan kolumbin (CID: 188289) dari Pubchem sedangkan protein DHFR-TS (PDB ID 2bl9) diperoleh dari Protein Data Bank, ligan dan protein diinteraksikan menggunakan HEX 8.0.0.0 dan divisualisasikan menggunakan discovery studio. Hasil yang diperoleh adalah enam residu asam amino yang berikatan dengan protein DHFR-TS. Pengikatan ini berdampak pada fungsi kerja protein DHFR-TS. Analisis fisikokimia menunjukkan bahwa ligan berperan sebagai donor dan akseptor sehingga protein yang terbentuk dan ligan menjadi sangat kuat. Interaksi ini juga didukung oleh residu asam amino yang bertindak sebagai pendukung dengan membentuk gaya Van der Waals di luar gaya ikatan hidrogen Van, pi-Alkil dan Pi juga memberikan dukungan dalam rangka meningkatkan kekuatan dan stabilisasi. Berdasarkan pembahasan dapat disimpulkan bahwa kandungan kolumbin pada Tinospora crispa L berpotensi sebagai terapi dan pengobatan malaria melalui penghambatan DHFR-TS.